Emergence of a partially disordered magnetic state driven by structural distortion in P d2DySn - Koushik P.; Choudhary M.; Kumar V.; Singh S.; Mukherjee K. (My University, 2025)
Frustrated magnetism, driven by competing exchange interactions, remains a pivotal topic in modern condensed-matter physics. In frustrated systems, observation of a partially disordered (PD) state where long-range magnetic order coexists with disorder is a unique phenomenon. Here, we focus on the emergence of a PD state and its underlying mechanism in a Heusler alloy, Pd2DySn. Our findings reveal that this alloy crystallizes in a cubic structure and undergoes a partial transformation to tetragonal phase at low temperatures. The static magnetization and heat capacity studies reveal three successive long-ranged antiferromagnetic transitions at ∼16, 12, and 6 K, respectively, while dynamic magnetization studies provide clear evidence for multiple cluster glass transitions, concomitant with the long-range ordering temperatures. This study demonstrates the coexistence between antiferromagnetic and glassy magnetic states, which is a relatively rare phenomenon in Heusler alloys. We propose that the emergence of the PD state stems from magnetic frustration induced by the structural distortion rather than geometrical frustration associated with triangular networks of magnetic ions as observed in other PD magnetic systems. © 2025 American Physical Society.